Instagram as a Development Strategy Brand Scarlett Whitening - Debra, Jessica; Owen, Miguel; Irwanto, Jacob; Herbert, Alvin; G, Nesya Rhenata (Jurnal VICIDI, 2022)
The use of social media as a development medium in improving product brands these days is huge and becoming a trend, especially among young people, so there is a lot of competition between brands on social media. This research was conducted with the aim of knowing the results and effectiveness of using social media in the form of Instagram as a method of developing a Scarlett Whitening Skincare brand strategy. In this study, Magari uses qualitative methods in examining the results of research conducted by other parties such as conducting research through the results of an Instagram survey of people’s views and opinions on the Scarlett Whitening brand and its products to obtain information and data on the effectiveness of Instagram as a strategy for developing the Scarlett Whitening brand. Keywords: Marketing, Strategy, Digital, Instagram, Skincare, Social Media